A ALFABETIZAÇÃO E O ENSINO FUNDAMENTAL DE NOVE ANOS: OS DESAFIOS DO 1º ANO - Câmara, Regina Celia dos Santos (2012)
The present study consists of a survey on the entry of children of six years in elementary education with a duration of nine years at four public schools in the state of São Paulo. As a foundation for the analysis of this educational policy, the theoretical approach is guided studies on the legislation, the concept of childhood, knowledge about the learning processes of reading and writing, training and practice of teachers. This is a qualitative research, structured analysis of propositions in official documents, in a questionnaire (for 25 teachers) and interviews with five of deepening teachers among those who answered the questionnaire. The purpose of the questionnaire and the interviews presented as objective: profiling and studying aspects of the professional life of teachers (research subjects); examine the ideas that guide their literacy practices; were prepared to analyze how this new reality, to discuss the progress and / or difficulties encountered in developing the pedagogical work with children from 1 year and analyze what they believe to be guaranteed for the successful education of these children. The research shows that include children six years in elementary school was, for the respondents, a positive measure, however, the deployment occurred without the preparation of schools and teachers. Teachers who took classes fell 1st year of the challenge, even without the structural conditions and proper training, organize time and school spaces. It was evident in the analysis, reporting about the practices of the teachers interviewed, the emphasis on literacy and literacy, although all recognize the importance of playful dimension in educational activities in the classroom. This emphasis stems from interpretations that make the determinations of the State Secretariat for Education and the indirect pressures perceived by them as the commitment to literacy in the 1st year of compulsory schooling, between them, the expectation of the school community parents and teachers the years following Elementary School. Finally, the data also show the need to ensure the training of educators, as well as discussions about the curriculum of classes for six years.